Evaluasi Aplikasi My Pertamina Menggunakan Technology Acceptance Model (TAM) (Studi Kasus SPBU Kota Kayuagung) - Wanhar; Firamon Syakti; Muhammad Sobri (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
My Pertamina is a form of Pertamina service in the form of a mobile-based application to make it easier for people to fill up fuel without using cash. The My Pertamina application began to be implemented by the Government since July 1, 2022, but its users are still a little visible in the fact that there are still few queues of people at the non-cash section of the post office and in reverse where people are still happy to stand in long queues with cash or without using the My Pertamina application. Community acceptance of the My Pertamina application is one of the factors that supports the continued use of the application. To find out the community's acceptance of the My Pertamina application, this research uses the TAM (Technology Acceptance Model) method, the TAM method consists of three perceptions, namely (i) perception of user convenience (PP), (ii) perception of usefulness (PK), and (iii) technology acceptance (PT). The data collection method uses a quantitative method by using a questionnaire as a tool to collect data on 50 users of the My Pertamina application in all SPBUs in Kota Kayuagung. The validity test shows that every question from the questionnaire is declared valid, the reliability test shows that the questionnaire is consistent and worthy of use, the user convenience perception variable has an average value of 4.48, the usefulness perception variable has an average value of 4.52, and the technology acceptance variable has a value an average of 4.49, this shows that respondents who have used the My Pertamina application have the perception of having received technology from using the My Per-tamina application. Keywords: My Pertamina, TAM, SPBU, BBM, Kuantitatif.